Exploring the potential of black soldier fly live larvae as a sustainable protein source for laying hens: A comprehensive study on egg quality - Arianna Cattaneo; Erminia Sezzi; Marco Meneguz; Roberto Rosà; Davide Santori; Sofia Cucci; Rosalba Roccatello; Francesca Grosso; Stefano Mercandino; Valeria Zambotto; Eugenio Aprea; Pavel Solovyev; et al. (Poultry Science)
Live insect larvae were recently proposed for use in laying hens in intensive chicken farming as an innovative form of environmental enrichment. This study aimed to evaluate the effect of laying hen age and feeding with live Black Soldier Fly larvae (BSFL) on egg quality attributes, i.e., chemical composition, fatty acid (FA) profile, and metabolic profile using nuclear magnetic resonance (NMR) spectroscopy. To this aim, 108 Lohman Brown hens were housed in 27 cages (9 replicates per treatment, 4 birds per pen) and monitored between 16 and 34 weeks of age. The hens were split into three experimental groups: a control group fed a commercial diet, and two experimental groups fed the same commercial diet plus 15% or 30% of live BSFL, as fed basis on the expected daily feed intake (DFI). The experimental treatments did not affect the egg and eggshell quality attributes. The supplementation with live BSFL did not influence the chemical composition in terms of macronutrients or the main NMR profiles of egg yolk and albumen. The FA profile of the egg yolk significantly changed as the eggs from hens fed BSFL presented higher rates of SFA and PUFA (P<0.05), lower rate of MUFA (P<0.001), and higher rates of C18:2n 6 (P<0.05) and C18:3 n3 compared to the control eggs (P<0.001). There were no significant differences in the ratio of n-6 to n-3 PUFA. The age of the hens strongly affected egg quality traits (P<0.001), mainly the egg weight, shell weight, shell thickness, eggshell-breaking strength, and eggshell redness (a*) and yellowness (b*), besides the metabolic profile of both egg yolk and albumen. Considering the interaction diet * age of hens, only a few significant effects occurred on egg quality attributes and FA profile. In conclusion, a supplementation with live BSFL up to 30% of DFI may be safely used in laying hen feeding without impairing egg quality.